Answer:
1. 9 + 3 - ( 2 + 4) = 6
2. 4^2 - (5 x (2 + 1)) = 1
Step-by-step explanation:
Here we must follow order of operations - that is commonly expressed as PEDMAS - First do parenthesis, then exponents, then divisions and multiplications from left to right and finally addition and subtraction from left to right.
If we follow this rule on 1)
9+3-2+4= 12-2+4= 10+4 = 14
Sow lets do it by parts
9+3-2+4= 12-2+4
if we can subtract 6 from 12 we would arrive to 6. This can be done id 2 and 4 are added first by 12-(2+4). So the result would be at:
9 + 3 - ( 2 + 4) = 6
In 2)
4^2 - 5 x 2 + 1 = 16-5x2+1 = 16-10 + 1 = 6+1 = 7
4^2 is always the first operation
16-5x2+1
Now if from 16 we subtract 15 we would obtain 1 so 5x2+1 must be equal 15 that can be done if we express it as:
16- 5x2+1
16- (5*(2+1)) = 5x3 = 15
So we have at the end:
4^2 - (5 x (2 + 1)) = 16 - 15 = 1